Fragmen Keramik Asing: Jejak Hubungan Dagang di Situs Kotacina - Stanov Purnawibowo (Balai Arkeologi Sumatera Utara, 2007)
AbstractCeramics Ware are found in Kotacina is one of the fact from the past about trade activities in Kotacina. Although that, wares only can be describe all of trade activities with another archaeological records which have the same context. At least wares were found in Kotacina can give a few describe about trade activities in the 12 th – 14 th Century in Kotacina.